Effect of Crystallization Temperature on Electrical Properties of Er3+/Yb3+–SrO.TiO2 Borosilicate Glass - Maheshwari A.; Singh N.K.; Parkash O.; Kumar D. (My University, 2025)
Er3+–Yb3+ doped 22[3SrO.2TiO2].30[2SiO2.B2O3] glass and glass–ceramics are developed and investigated for their electrical properties. The degree of crystallization is varied by means of crystallization temperature ranging from 600 to 1000°C. In glass–ceramic samples, two major crystalline phases, Sr3Ti2O7 and TiO2, are confirmed by diffraction analysis. The best crystallized glass–ceramic (crystallization temperature 950°C) sample shows 100–1 50 times lower impedance in temperature range, 200–300°C, than the uncrystallized glass. Electrical relaxation corresponding to the crystalline phase can be isolated in frequency domain. The glass–ceramic shows a 10–100 times higher dielectric constant than the glass in lower frequency range. This dielectric constant and dissipation factor increase with increasing temperature beyond a threshold value. Curie temperature was not visible in the measured temperature range. © 2015 The American Ceramic Society and Wiley Periodicals, Inc